The role of internet parenting on internet addiction among adolescents - Auraningtyas, Intan; Arshanty, Ilma Rizqa; Rahmawati, Riva Tri; Trisnawati, Trisnawati (Psychological Research and Intervention, 2023)
Various age groups have used the internet, including adolescents. Uncontrolled internet use can lead to psychological problems, such as internet addiction. One of the factors causing internet addiction is the lack of parental mediation in adolescents' internet activities, but some previous studies related to internet parenting showed inconsistent results. This study aims to determine the effect of internet parenting on internet addiction among junior high school adolescents in Yogyakarta. It is a quantitative survey study using the Indonesian version of the Internet Addiction Test scale (a=0.888) and the Internet Parenting scale (a=0.921). The data were collected from 171 junior high school students in Yogyakarta (ages 12-17) by online questionnaire and analyzed using linear regression in JASP 0.17.1. The research findings show an insignificant predictor of internet parenting to internet addiction (F=0.045, P=0.833 > 0.05). This shows that although internet parenting may have a role in preventing internet addiction in adolescents, other factors such as peer influence should also be considered in explaining the phenomenon of internet addiction among junior high school adolescents in Yogyakarta.